Philosophical and Comparative Analysis of Scientific Thought in China to Study the Activity of the SCO - Borisenko, Olga (International Journal of Economics and Financial Issues, 2016)
The article analyzes the strategic partnership between the Russian Federation and China, as a member of the Shanghai Cooperation Organization (SCO), and we can see analysis of scientific works in China. In this article author said that all the SCO studies in China can be divided into two categories, where one of them is the real political dynamics studies, the other - focuses on theoretical questions. Its creation has affected not only the solution of border issues of China with neighboring countries. The emergence of new international non-governmental organizations focused on dialogue contribute to globalization and challenges against the backdrop of the current international image of the world. Directly in China studies at the SCO is of great interest not only in the scientific public, but also in society. This is due to the fact that the Shanghai Cooperation Organization is the only international and regional organizations, which was established on the initiative of not only China, but also with the regional headquarters located in China. The SCO creation has affected not only the solution of border issues of China with neighboring countries, but also largely contributed to peace and stability in the region. Keywords: China, Shanghai Cooperation Organization, dialog, strategic partnership, stability JEL Classifications: C62, O18, P13